2021
DOI: 10.1590/2675-2824069.20-009lst
|View full text |Cite
|
Sign up to set email alerts
|

Wave climate and power distribution around a rocky island: Alcatrazes, Brazil

Abstract: We investigate the distribution of the wave power around the Alcatrazes island, a protected marine reserve in southeastern Brazil, located at 20 nautical miles from the coast of São Sebastião/SP. A 14-year wave time series (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) extracted from the global WaveWatch III model, was used to obtain the offshore wave climate. Based on the wave climate, a wave propagation model (Delft3D) was applied in order to obtain nearshore information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In the totality of 107 scientific publications on ORE in Brazil, a total of 46 include offshore wind subjects, including theoretical, technical and economic potential assessment [22,28,[44][45][46], resource complementarity including hydropower, offshore wind and offshore solar [47,48], offshore wind environmental [34] and social [49] impacts and regulatory aspects [36]. Research about wave energy in Brazil started in 2000, focusing mainly on wave resource potential [50,51], wave-to-wire modeling [52], geometry optimization [53] and control systems and strategies [30,[54][55][56], experimental tests including dry tests [57] and reduced scale models in wave tank [58], economic feasibility [27] and environmental aspects [59] of WECs. Some works, including [31,60] and [23], are examples of studies that addressed tidal, ocean current and OTEC, respectively.…”
Section: Brazilmentioning
confidence: 99%
“…In the totality of 107 scientific publications on ORE in Brazil, a total of 46 include offshore wind subjects, including theoretical, technical and economic potential assessment [22,28,[44][45][46], resource complementarity including hydropower, offshore wind and offshore solar [47,48], offshore wind environmental [34] and social [49] impacts and regulatory aspects [36]. Research about wave energy in Brazil started in 2000, focusing mainly on wave resource potential [50,51], wave-to-wire modeling [52], geometry optimization [53] and control systems and strategies [30,[54][55][56], experimental tests including dry tests [57] and reduced scale models in wave tank [58], economic feasibility [27] and environmental aspects [59] of WECs. Some works, including [31,60] and [23], are examples of studies that addressed tidal, ocean current and OTEC, respectively.…”
Section: Brazilmentioning
confidence: 99%
“…Brazil has a small number of oceanic islands and a large number of islands near the coastline that contain unique biological species. The Alcatrazes Archipelago, located 35 km off the São Paulo state coastline, presents several endemic species . We have recently performed surveys of microbial species from Alcatrazes island, with a focus on endophytic bacteria and fungi, and observed that the endophyte community of endemic plants on this island is highly specific .…”
mentioning
confidence: 99%
“…Together, they act as mitigating elements and reflect a more stable environment in the north and towards the coast, due to the indirect incidence of waves as well as energy loss by the decreasing bathymetry. Furthermore, regions are more energetic in the south, with waves varying slightly through the seasons and years (Takase et al, 2021). These factors rule the deposition process in the archipelago, forming sediment features that are sustained over time.…”
Section: Hydrographic and Sedimentological Analysesmentioning
confidence: 99%
“…Spatially, while the northwest and northeast parts were predominantly characterized by finer grains and poor CaCO3 content, the south (i.e., part exposed to the open ocean), could be distinguished in two regions: the eastern portion, that is similar to the first two, and the western, with presence of coarse sands and higher CaCO3 concentrations. According to Takase et al (2021), this region is highly influenced by energetic waves which explains the sediment configuration by the displacement of finer grains to the east. Consequently, the heterogeneity of habitats in the exposed part resulted in a more diverse fauna in comparison to the northern area.…”
Section: Oceanographic Features Driving the Community Dynamicsmentioning
confidence: 99%